Comparison of glucagon-like peptide-1 receptor agonists vs. placebo on any cardiovascular events in overweight or obese non-diabetic patients: a systematic review and meta-analysis - Kelkar, Raveena; Barve, Nishad A.; Kelkar, Rohan; Kharel, Sanjeev; Khanapurkar, Shalmi; Yadav, Rukesh (Frontiers in Cardiovascular Medicine, 2024)
Glucagon-like peptide 1 receptor agonists (GLP-1 RA) have been extensively used to treat obesity in recent years. These novel drugs are effective at reducing body weight and also the risk of major adverse cardiovascular events in individuals with type 2 diabetes. However, the data of its efficacy in reducing cardiovascular events in individuals without type 2 diabetes is not as robust. We aim to update and conduct a systematic review and meta-analysis to assess the same.The study was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guideline. Researchers searched PubMed, EMBASE, and Clinicaltrails.gov for English literature from inception to 2024. Randomized Controlled trails enrolling adult participants (age ≥ 18 years) who are overweight or obese (BMI>25 Kg/m 2 ) with a comparison of all cardiovascular events between patients taking GLP1-RA and placebo were included. The analysis was done by Revman version 5.4.A total of 17 RCTs among 34,419 participants were included in the analysis. The pooled risk ratio from 17 studies illustrated that patients with GLP-1 RA had a significantly lower risk of cardiovascular events compared to patients who had a placebo (RR=0.75; 95% confidence interval 0.64 to 0.89, p-value=0.0008). Semaglutide was found to have a statistically significant greatest risk reduction than other drug types.This meta-analysis found that GLP-1 RA significantly reduced all types of cardiovascular events in overweight and obese patients without diabetes. Semaglutide was found to be superior to others in CV event reductions. But still, the results of ongoing trials are needed.